A Study on the Prospects of the Korea Beauty Industry - Hee-Kyung Lim, Hye-Jin Kwon, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The development of IT industry is playing an important role in the prevention of the COVID-19 infection in Korea. The development of IT industry is used in various fields. The beauty industry in the era of the 4th Industrial Revolution can identify the racial, regional and individual characteristics of customers through the use of big data with the AI system. It is also expected that such development will bring a change in the creation of new jobs and occupations in the service industry. Therefore, it is necessary to establish an environment that enables the development of nurturing education and creativity of outstanding individuals who will lead new business trends. In addition, a beauty-related industry that can meet the desire of new elderly consumers throughout the society is required. It is expected that the beauty industry in Korea will require a service that combines self-development, convenience and plays for companies, workers and consumers in future.